2001
DOI: 10.1300/j150v08n03_07
|View full text |Cite
|
Sign up to set email alerts
|

Personal Values and Media Usefulness of Mature Travelers

Abstract: This study expands our understanding of the mature market by investigating the importance of nine personal values and the usefulness of 19 media sources in a travel context. Findings from a survey of 235 travelers are reported. Results suggest that the three dominant values are Self-Respect, Warm Relations with Others, and Security. The most useful media sources include recommendations from family/friends, feature stories in mass media, and quasi-governmental outlets. Implications for marketing professionals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…This conformed to the research of Capella and Greco (1989) who found that the most important sources of tourism information that helped the elderly to decide on their holiday destination is their family. This was the same as the study of Fall and Knutson (2001) who found that the most beneficial source of travel information for the elderly was word of mouth from friends and family which was aligned with the study of Patterson (2007) who studied the information sources used by the elderly to decide on their travel destinations in which they seemed pay attention to word of mouth and personal experiences.…”
Section: Results Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This conformed to the research of Capella and Greco (1989) who found that the most important sources of tourism information that helped the elderly to decide on their holiday destination is their family. This was the same as the study of Fall and Knutson (2001) who found that the most beneficial source of travel information for the elderly was word of mouth from friends and family which was aligned with the study of Patterson (2007) who studied the information sources used by the elderly to decide on their travel destinations in which they seemed pay attention to word of mouth and personal experiences.…”
Section: Results Discussionsupporting
confidence: 73%
“…Research by Capella and Greco (1998) studied a sample group aged over 60 years old in the middle part of New York and found that the most important sources of information that helped elderly to set up their holiday destinations are first, family, second, from past experiences, friends, magazines, TV, consumer publications, direct mail, point of purchase displays, neighbors, radio, and tour agents respectively. The study by Fall and Knutson (2001) found that the top beneficial sources of information for aging tourists are continual suggestions from friends and relatives, second, from TV travel programs, brochure/direct mail, government tourism media, articles in newspapers, articles in magazines, car clubs, internet websites, travel agents, TV advertisements, newspaper advertisements, product exhibitions, magazine advertisements, radio spots and CD-Roms respectively. The research by Kim et al ) 2007 ( aimed to check the relationship between the travel motivation and the information searching behavior of the tourists in three segments.…”
Section: Concept Related To the Key Tourism Information Source That Amentioning
confidence: 99%
“…As a result, research on Internet use in tourists' media choice has steadily increased, and has received much attention from both academics and practitioners. Fall and Knutson (2001) examined perceived media usefulness among mature travelers, and found that 27% of respondents (older than 55) considered Internet websites very useful in making travel decisions. Their results indicate that feature stories in magazines, newspapers, and television are very useful, especially in determining travel destination, with word of mouth (WOM) the most influential.…”
Section: Media and Travel Information Searchmentioning
confidence: 99%
“…More recently, Blamey (1997) noted that personal values are relevant across different situations and their limited number makes them economical measures in the field of psychographics and marketing. Some researchers, including Fall (2001) and Muller (1991;2000), have investigated personal values within the context of tourism. Fall (2001), for example, highlighted the role of personal values in marketing communications and found that travellers' hedonic and achievement personal values influenced the use of interpersonal media sources.…”
mentioning
confidence: 99%
“…Some researchers, including Fall (2001) and Muller (1991;2000), have investigated personal values within the context of tourism. Fall (2001), for example, highlighted the role of personal values in marketing communications and found that travellers' hedonic and achievement personal values influenced the use of interpersonal media sources. Muller (1995) investigated the role of personal values within the context of destination marketing in relation to tourists' beliefs about the security, recreational and avoidance aspects of a visit to a destination.…”
mentioning
confidence: 99%